An ethnographic exploration of studio production practice - McGrath, Sean; Hazzard, Adrian; Chamberlain, Alan; Benford, Steve (2016)
Tools for music production range from full scale digital production workstations to context-driven plugins. There are a number of inherent challenges to address in supporting users at different stages of work and at different levels of technical skill, utilizing both legacy and novel tools. We present findings from ethnographic encounters of music production at work and discuss some of the challenges of designing and developing systems for different types of users. We explore the issues of collaboration, shared ownership and a growing need for tools to support automation and intelligent music making as a practice. The work explores the use of technology in a real world, working studio environment.